Assessment of IgG3 as a serological exposure marker for Plasmodium vivax in areas with moderate–high malaria transmission intensity - Tayipto, Yanie; Rosado, Jason; Gamboa, Dionicia; White, Michael T.; Kiniboro, Benson; Healer, Julie; Opi, D. Herbert; Beeson, James G.; Takashima, Eizo; Tsuboi, Takafumi; Harbers, Matthias; Robinson, Leanne; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
A more sensitive surveillance tool is needed to identify Plasmodium vivax infections for treatment and to accelerate malaria elimination efforts. To address this challenge, our laboratory has developed an eight-antigen panel that detects total IgG as serological markers of P. vivax exposure within the prior 9 months. The value of these markers has been established for use in areas with low transmission. In moderate–high transmission areas, there is evidence that total IgG is more long-lived than in areas with low transmission, resulting in poorer performance of these markers in these settings. Antibodies that are shorter-lived may be better markers of recent infection for use in moderate–high transmission areas. Using a multiplex assay, the antibody temporal kinetics of total IgG, IgG1, IgG3, and IgM against 29 P. vivax antigens were measured over 36 weeks following asymptomatic P. vivax infection in Papua New Guinean children (n = 31), from an area with moderate–high transmission intensity. IgG3 declined faster to background than total IgG, IgG1, and IgM. Based on these kinetics, IgG3 performance was then assessed for classifying recent exposure in a cohort of Peruvian individuals (n = 590; age 3–85 years) from an area of moderate transmission intensity. Using antibody responses against individual antigens, the highest performance of IgG3 in classifying recent P. vivax infections in the prior 9 months was to one of the Pv-fam-a proteins assessed (PVX_125728) (AUC = 0.764). Surprisingly, total IgG was overall a better marker of recent P. vivax infection, with the highest individual classification performance to RBP2b1986-2653 (PVX_094255) (AUC = 0.838). To understand the acquisition of IgG3 in this Peruvian cohort, relevant epidemiological factors were explored using a regression model. IgG3 levels were positively associated with increasing age, living in an area with (relatively) higher transmission intensity, and having three or more PCR-detected blood-stage P. vivax infections within the prior 13 months. Overall, we found that IgG3 did not have high accuracy for detecting recent exposure to P. vivax in the Peruvian cohort, with our data suggesting that this is due to the high levels of prior exposure required to acquire high IgG3 antibody levels.